2020
DOI: 10.4314/jcmphc.v32i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Stress among Bankers in Enugu State South-East Nigeria

Abstract: Background: The work environment is rapidly changing and in recent times, occupational stress poses a threat to the health, morale and productivity of workers and the organization. This study sought to determine the prevalence and predictors of stress among bankers in a south-eastern state of Nigeria. Methods: A descriptive cross-sectional study was carried out among 370 bankers in Enugu State, Nigeria using the Health, Safety, Executive (HSE) management standards indicator tool. Multistage sampling method was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Onigbogi and Banerjee (2019) reported a prevalence of 61.9% of psychosocial stress among healthcare workers in Nigeria. This high prevalence of stress in Nigeria was confirmed by recent studies with 47% in Enugu State (Okwor, 2020) and 62% in Oyo State (Alao et al, 2023). These show higher prevalence rate compared to other developing countries such as Rwanda (15.3%) (Nwankwo et al, 2017), Ghana (17%) (Alhassan & Poku, 2018) and Uganda (21.5%) (Ndejjo et al, 2015).…”
Section: Introductionsupporting
confidence: 58%
“…Onigbogi and Banerjee (2019) reported a prevalence of 61.9% of psychosocial stress among healthcare workers in Nigeria. This high prevalence of stress in Nigeria was confirmed by recent studies with 47% in Enugu State (Okwor, 2020) and 62% in Oyo State (Alao et al, 2023). These show higher prevalence rate compared to other developing countries such as Rwanda (15.3%) (Nwankwo et al, 2017), Ghana (17%) (Alhassan & Poku, 2018) and Uganda (21.5%) (Ndejjo et al, 2015).…”
Section: Introductionsupporting
confidence: 58%
“…An average score of 1-2 showed that they were likely to be already suffering from high levels of stress because of demand-resource imbalance or be at risk of it. They categorized a score of 3 as neutral (Okwor et al,2020).…”
Section: Tools Of Data Collectionmentioning
confidence: 99%
“…To lower this churn and boost retention, organisations must proactively address these issues and develop effective employee satisfaction strategies. According to research by Okwor et al (2020), burnout is a significant factor influencing employee turnover and is common among finance professionals. Burnout is strongly correlated with long hours, high demands, and little job control and is associated with significantly higher intentions to leave among workers in the finance industry.…”
Section: Introductionmentioning
confidence: 99%